2022
DOI: 10.3390/ma15196579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Material Flow Gradients on Mechanical Performances of Friction Stir Welded AA6082-T6 Joints

Abstract: The temperature and material flow gradients along the thick section of the weld seriously affect the welding efficiency of friction stir welding in medium-thick plates. Here, the effects of different gradients obtained by the two pins on the weld formation, microstructure, and mechanical properties were compared. The results indicated that the large-tip pin increases heat input and material flow at the bottom, reducing the gradient along the thickness. The large-tip pin increases the welding speed of defect-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The reduction in heat input reduces the loss of strength, while insufficient material flow at the bottom joint leads to forming of small-sized cavities that reduce elongation. 65 It worth noticing is that grain boundaries hinder the occurrence of crack propagation within the microstructure, and therefore, stress and strain distribution improve resulting in the development of ductility. 66 An adequate and continuous IMC layer with adequate thickness is another critical factor to improve the strength of the weld interface during the P-FSSW process.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in heat input reduces the loss of strength, while insufficient material flow at the bottom joint leads to forming of small-sized cavities that reduce elongation. 65 It worth noticing is that grain boundaries hinder the occurrence of crack propagation within the microstructure, and therefore, stress and strain distribution improve resulting in the development of ductility. 66 An adequate and continuous IMC layer with adequate thickness is another critical factor to improve the strength of the weld interface during the P-FSSW process.…”
Section: Resultsmentioning
confidence: 99%
“…During FSP, a non-consumable rotating tool with a pin and a shoulder is used to process a single piece of material, resulting in specific property enhancements [2][3][4]. The shoulder generates heat, because of friction, to plasticize the material, while the rotating tool pin inside the material causes the flow of material under elevated temperature conditions [5][6][7][8]. This frictional heat causes the flow of work-piece material around the tool periphery [9].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the size of the incoherent intermetallic particles and the volume fraction decreased towards to the center of the layer. Ma et al [21] investigated the effects of temperature on mechanical performances of friction-stir-welded aluminum alloy joints. It was found that the reduction in the gradient along the thickness due to the pinhole increased heat input and material flow at the bottom.…”
Section: Introductionmentioning
confidence: 99%